More than a phase: The impact of sexual orientation, age, and prescriptive stereotype violation on coworker perceptions - Christman, Gillian K (My University, 2025)
As LGBTQIA+ (people attracted to same-sex persons or possess diverse sexual orientations and gender identities) employees gain visible workplace representation, more research is needed to explore how workplace relationships change when employees are open about their sexual orientation (Alvarado et al., 2023). Based on expectancy violation theory (Burgoon, 1978), prejudice may be attached to those without traditional sexual orientations at work because of violated expectations from other employees that do not match the view of a “stereotypical worker”. Despite rising acceptance of LGBTQIA+ identities (Early et al., 2020), workers may still face backlash and understanding this backlash is imperative to fostering inclusive workplaces. Prescriptive stereotype theory suggests that workers engaging unexpected behaviors based on their social identities, may receive negative reactions towards their character (seeing them as less competence and less warm), which may subsequently lead their coworkers to ostracize them. Replicating and extending Hanrahan et al. (2023) and evaluating a new outcome of ostracism and avoidance behaviors (Liu, 2019) on 487 full-time employees, this study found that older, gay workers had more violation ratings compared to other groups, along with higher rates of ostracism and avoidance behaviors by participants. Violators of age identity prescriptive stereotypes were also seen as less warm regardless of age, but on its own older age groups were seen to be more violating than younger age groups. These results help address interventions and further understanding of how to address needs of older LGBTQIA+ workers.
Keywords: age, sexual orientation, expectancy violation, prescriptive stereotypes, workers